Allu tells some thoughtful stories - Pavel Allu; Valentina Dedyk; Alexander King (Alexander King, 2013)
Allu tells more stories. Some long pauses. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra. Learned Russian as 4th language starting in grad school and extensive residence in Kamchatka (1995 5mos, 1997-98 17 months). Had very good conversational skills by summer 1997 and fluent by early 1998, at least in listening. Has thick American accent. Knows a few words of Koryak for social situation.